Productive Efficiency of Milk Production in Tamil Nadu - Dhanabalan, M. (Indian Journal of Marketing, 2009)
Agriculture has always been the backbone of the Indian economy. It provides employment to around 60 percent of the total work force. Agricultural growth has direct impact on poverty eradication. The change in the agricultural sector, whether positive or negative, will have a multiplier effect on the entire economy. Besides, the allied sector like horticulture, animal husbandry, dairy and fisheries have an important role in improving the over all economic conditions of rural India. To maintain the ecological balance, there is need for sustainable and balanced development of agriculture and allied sectors. From our first plan onwards, planners have given priority to allied sector for the economic development of the rural sector. Dairy farming is described as a small industry which provides gainful employment opportunities. It comprises of about six per cent of the national income.